2006
DOI: 10.1038/nm1521
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus modulates intestinal pain and induces opioid and cannabinoid receptors

Abstract: Abdominal pain is common in the general population and, in patients with irritable bowel syndrome, is attributed to visceral hypersensitivity. We found that oral administration of specific Lactobacillus strains induced the expression of mu-opioid and cannabinoid receptors in intestinal epithelial cells, and mediated analgesic functions in the gut-similar to the effects of morphine. These results suggest that the microbiology of the intestinal tract influences our visceral perception, and suggest new approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
491
0
18

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 696 publications
(525 citation statements)
references
References 15 publications
16
491
0
18
Order By: Relevance
“…In addition, microbiota-related markers should be investigated in greater detail. Recently, Rousseaux and colleagues 57 reported that certain…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microbiota-related markers should be investigated in greater detail. Recently, Rousseaux and colleagues 57 reported that certain…”
Section: Discussionmentioning
confidence: 99%
“…They also have the potential to modulate pain perception. Lactobacillus acidophilus has been reported to modulate expression of cannabinoid receptors and reduce abdominal pain in rodents (Rousseaux et al, 2007).…”
Section: Microbiota and Humoral Responsesmentioning
confidence: 99%
“…Oral probiotic preparations aimed at restoring the " healthy commensal biota balance " have been met with much enthusiasm by IBS patients, and studies have shown Lactobacilli and Bifi dobacteria preparations both modulate immune function and improve IBS symptoms ( 21 -23 ). Furthermore, rectal infusion of bacteria, particularly the Lactobacillus strains, also induces analgesic eff ects, possibly due to upregulation of μ -opioid receptors on epithelial cells rather than direct actions on GI nerves ( 24,25 ). Recent studies indicate that treatment with a nonabsorbable broad spectrum antibiotic provided relief for IBS-D patients ( 26,27 ).…”
Section: Role Of Microbiota In Ibsmentioning
confidence: 99%